Of cecropias, snarks and boojums - Sheil, Douglas; Padmanaba, M. (2011)
We reply to Webber et al. (2011). Our study, Sheil and Padmanaba (2011), was a preliminary assessment of the alien Neotropical tree Cecropia around Bogor, West Java, Indonesia. We highlighted the need for low-cost assessment approaches for addressing alien species and considered what might be achieved by local actors with limited resources. We successfully characterised the local distribution of Cecropia and identified, addressed and illustrated various concerns. Based on these results we asked how such studies might be useful and how they could be improved. Webber et al. criticise our study but fail to engage with its goals. Certainly, low-input local approaches lack the sophistication and rigour of larger international efforts, but such comparisons are unhelpful. Aside from a number of misunderstandings, we find Webber et al.’s principal arguments overstated, and unsupported by published information. The evidence that Cecropia causes harm is unconvincing; species-level identification is overemphasised; and the insistence on completing detailed research before considering management options is problematic. We offer some positive conclusions and repeat our plea for the development of effective low-input methods for evaluating and addressing naturalised organisms.